نسبة انتشار غياب الأسنان ونماذجه لدى عينة من مرضى التقويم السوريين - حداد رانيه (Latakia University Journal -Medical Sciences Series, 2016)
هدف البحث: 1- تحديد نسب انتشار غياب الأسنان الدائمة في عينة من مرضى التقويم في المجتمع السوري 2- ونماذج هذا الغياب. المواد والطرائق: تمت دراسة سجلات 623 مريض بأعمار 12-34 من مراجعي قسم تقويم الأسنان في كلية طب الأسنان/جامعة دمشق خلال السنوات الثلاثة الأخيرة (2011-2014) لإحصاء نسبة المرضى الذين لديهم غياب لسن دائمة أو أكثر. النتائج: 1- كانت نسبة انتشار غياب الأسنان7.10% من العينة المدروسة (7.49% للإناث و 6.35% للذكور). الذكورُ أقل تأثراً من الإناث بنسبة 1:1.18 دون أي فارق إحصائي بين الجنسين (P = 0.063). 2- السن الأكثر تعرضاً للغياب هي الرباعية العلوية (56.52%)، والسن الأقل غياباً هي الرحى الأولى العلوية (0.87%). وكانت نسبة الغياب في الفك العلوي أعلى منها في الفك السفلي بفارق دال إحصائياً (P=0.041) وفي الأسنان الأمامية أكثر منها في الخلفية بفارق دال إحصائياً (P=0.009). الاستنتاجات: إن نسبة انتشار غياب الأسنان التي أظهرتها هذه الدراسة تقع ضمن المدى الذي نُشِر في الأدبيات الطبية. ونماذجه متوافقة مع نماذج معظم المجتمعات Aims of study: 1-To determine the prevalence and 2- the pattern of hypodontia in the permanent dentition in a sample of Syrian orthodontic patients who sought orthodontic treatment. Materials and Methods: The orthodontic records of 623 patients aged 12 to 34, who sought orthodontic treatment in the Department of Orthodontics, Dental faculty/Damascus University, during the last three years (2011-2014), were investigated to establish the prevalence of patients with one or more permanent missing teeth. Results: 1-The prevalence of hypodontia was 7.10% of the studied sample (7.49% in females, and 6.35% in males). Males were less affected than females with a ratio of 1:1.18 with no significant differences between genders (P = 0.063). 2-The most common missing tooth was maxillary lateral incisor (56.52%), the least common missing tooth was maxillary first molar (0.87%). Missing in the maxillary jaw was significantly more frequent than the mandible (P=0.041( with significantly more anterior teeth missing than posterior teeth (P=0.009). Conclusions: The prevalence of hypodontia showed in this study was within the range published in the literature. The patterns are similar to most reported patterns in the literature. .